The impact of the COVID-19 pandemic on waiting times for elective surgery patients: A multicenter study - Uimonen, Mikko; Kuitunen, Ilari; Paloneva, Juha; Launonen, Antti P.; Ponkilainen, Ville; Mattila, Ville M. (PloS one, 2021)
A concern has been that health care reorganizations during the first COVID-19 wave have led to delays in elective surgeries, resulting in increased complications and even mortality. This multicenter study examined the changes in waiting times of elective surgeries during the COVID-19 pandemic in Finland. Data on elective surgery were gathered from three Finnish public hospitals for years 2017-2020. Surgery incidence and waiting times were examined and the year 2020 was compared to the reference years 2017-2019. The mean annual, monthly, and weekly waiting times were calculated with 95% confidence intervals (CI). The most common diagnosis groups were examined separately. A total of 88 693 surgeries were included during the study period. The mean waiting time in 2020 was 92.6 (CI 91.5-93.8) days, whereas the mean waiting time in the reference years was 85.8 (CI 85.1-86.5) days, resulting in an average 8% increase in waiting times in 2020. Elective procedure incidence decreased rapidly in the onset of the first COVID-19 wave in March 2020 but recovered in May and June, after which the surgery incidence was 22% higher than in the reference years and remained at this level until the end of the year. In May 2020 and thereafter until November, waiting times were longer with monthly increases varying between 7% and 34%. In gastrointestinal and genitourinary diseases and neoplasms, waiting times were longer in 2020. In cardiovascular and musculoskeletal diseases, waiting times were shorter in 2020. The health care reorganizations due to the pandemic have increased elective surgery waiting times by as much as one-third, even though the elective surgery rate increased by one-fifth after the lockdown.